IN FARABI’S VIEWS, THE IMPORTANCE OF IMAGINATION IN HAPPINESS (American Journal of Research in Humanities and Social Sciences, 2023)
This article reflects the philosophical ideas of Abu Nasr Farabi, who is viewed one of the fantastic thinkers of the Eastern world, about man and happiness, and his thoughts about the importance of imagination in experiencing happiness. Moreover, Farabi's principles of everlasting and general happiness are also reflected.